Clinical and immunological comparisons of the results of testing for COVID-19 of employees of an outpatient medical organization of a large industrial centre during a pandemic - O. O. Obukhova; A. N. Trunov; O. M. Gorbenko; A. P. Shvayuk; T. I. Ryabichenko; G A. Skosyreva; A. V. Obukhov (Юг России: экология, развитие, 2021)
Aim. To determine the presence or absence of specific IgG antibodies against SARS-CoV-2 antigens in outpatient clinic staff and to compare clinical and immunological features from April to August 2020.Materials and Methods. The control group comprised 386 employees of the Novosibirsk City Clinical Polyclinic №13.The determination of IgG antibodies against SARS-CoV-2 antigens in blood serum was performed by using the ELISA method. A real time method of reverse transcription and polymerase chain reaction was used to extract RNA SARS-CoV-2 from nasopharyngeal and oropharyngeal swabs.Results. Specific IgG antibodies against SARS-CoV-2 antigens were detected in 32 (8.42%) employees of the polyclinic. Antibodies were not detected in 91.58% of employees. 9 members (28.12%) had clinical symptoms of varying degrees of disease severity in the group of employees with the presence of antibodies, 4 members of this group (12,51%) had bilateral community-acquired pneumonia with signs of COVID infection, another 5 members (15.61%) with antibodies had signs of ARVI of mild and moderate severity. RNA SARS-CoV-2 in the group of employees with the presence of antibodies and clinical implications was not detected in any case; 23 (71.88%) members with the presence of IgG-antibodies did not have clinical implications of the disease.Conclusion. The presence of specific antibodies against SARS-CoV-2 in employees with clinical implications of COVID-19 without detection of the RNA virus in the biological material is a retrospective confirmation of the etiology of the transferred infection. The detection of specific antibodies in persons who did not have clinical implications can serve as confirmation of the asymptomatic course of the transferred coronavirus infection.